2016
DOI: 10.18261/issn.1894-8693-2016-02-05
|View full text |Cite
|
Sign up to set email alerts
|

Nightlife Partnership Policing - (Dis)trust Building Between Bouncers and the Police in the War on Gangs

Abstract: This article contributes to the research on trust in policing by examining how private security actors (bouncers) experience the police as a partner in informal policing networks emerging as part of the 'war on bikers and gangs' in Danish nightlife. While much international research about partnership policing has employed a police perspective and a top-down approach, thus emphasizing organizational ties between policing bodies, this article uses a bottom-up, interactional approach, with a focus on bouncers' ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
(40 reference statements)
2
7
0
Order By: Relevance
“…Giacomantonio, 2015). These findings align with previous research, which has found that information sharing also relies on informal activities and personal relationships (Dupont, 2004, O'Neill and McCarthy, 2014, Cotter, 2015, Søgaard et al, 2016, and 'that the underlying relational properties of security networks […][make] it difficult to distinguish between formal and informal ties' (Whelan, 2016). …”
Section: Bridging Systemic Boundaries Of Information Flowsupporting
confidence: 90%
See 2 more Smart Citations
“…Giacomantonio, 2015). These findings align with previous research, which has found that information sharing also relies on informal activities and personal relationships (Dupont, 2004, O'Neill and McCarthy, 2014, Cotter, 2015, Søgaard et al, 2016, and 'that the underlying relational properties of security networks […][make] it difficult to distinguish between formal and informal ties' (Whelan, 2016). …”
Section: Bridging Systemic Boundaries Of Information Flowsupporting
confidence: 90%
“…Pluralisation characterises contemporary policing, and partnerships as well as networked security governance between state and non-state actors have been examined empirically (Gundhus et al, 2008, Nøkleberg, 2016, Søgaard et al, 2016. This study explores the co-ordination of state powers in the multi-agency Lime project.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas the law and public authorities feel abstract and absent in many nightlife environments (Søgaard, Houborg, & Tutenges, 2017), patrons are very much present and their commands loud and obvious.…”
Section: Workplace Environment and Coping Strategiesmentioning
confidence: 99%
“… 3. In recent decades, Danish police have played a key role in enforcing an informal ban on outlaw bikers and gang-related individuals in Danish nightlife, regardless of whether or not they behave in an orderly manner (see Søgaard, Houborg, & Tutenges, 2016). …”
mentioning
confidence: 99%